Can dynamic occupancy models improve predictions of species' range dynamics? A test using Swiss birds. (19th June 2021) - Briscoe, Natalie J.; Zurell, Damaris; Elith, Jane; König, Christian; Fandos, Guillermo; Malchow, Anne‐Kathleen; Kéry, Marc; Schmid, Hans; Guillera‐Arroita, Gurutzeta
Abstract: Predictions of species' current and future ranges are needed to effectively manage species under environmental change. Species ranges are typically estimated using correlative species distribution models (SDMs), which have been criticized for their static nature. In contrast, dynamic occupancy models (DOMs) explicitily describe temporal changes in species' occupancy via colonization and local extinction probabilities, estimated from time series of occurrence data. Yet, tests of whether these models improve predictive accuracy under current or future conditions are rare. Using a long‐term data set on 69 Swiss birds, we tested whether DOMs improve the predictions of distribution changes over time compared to SDMs. We evaluated the accuracy of spatial predictions and their ability to detect population trends. We also explored how predictions differed when we accounted for imperfect detection and parameterized models using calibration data sets of different time series lengths. All model types had high spatial predictive performance when assessed across all sites (mean AUC > 0.8), with flexible machine learning SDM algorithms outperforming parametric static and DOMs. However, none of the models performed well at identifying sites where range changes are likely to occur. In terms of estimating population trends, DOMs performed best, particularly for species with strong population changes and when fit with sufficient data, while static SDMs performed very poorly. Overall, our study highlights the importance of considering what aspects of performance matter most when selecting a modelling method for a particular application and the need for further research to improve model utility. While DOMs show promise for capturing range dynamics and inferring population trends when fitted with sufficient data, computational constraints on variable selection and model fitting can lead to reduced spatial accuracy of predictions, an area warranting more attention. Abstract : Using a long‐term dataset on 69 Swiss birds, we show that dynamic occupancy models show promise for capturing range dynamics and inferring population trends when fitted with sufficient data, outperforming "static" species distribution models. But computational constraints on variable selection and model fitting can lead to reduced spatial accuracy of predictions, an area warranting more attention.